Factors Contributing to Absenteeism Among 4ps Beneficiary-Students in Selected Elementary Schools, Can-Avid District - Hicao, Jessica L.; Irasga, Mary Rose D.; Hobayan, Juvy Cris A.; Adina, Jofrelyn B.; Baldelobar, Ester A.; Goden, Rhea Rose J.; Diaz, Jill C.; Busa, Ailyn C.; Hobayan, Rosechill D.; Lascano Jr., Juanito E.; Quiloña, Janice Dyan G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study investigates absenteeism among 4Ps beneficiary-students in selected elementary schools, Can-avid District, that focus on factors influencing attendance patterns. The research aims to identify key factors impacting absenteeism, understand their implications, and propose targeted solutions for improving attendance and improve academic performance of students. Through a quantitative-descriptive correlational design, data was collected on attendance levels, parental education, distance to school, health conditions, and parental involvement. The analysis revealed a positive commitment to education among students, with high attendance rates emphasizing a conducive learning environment. Significant positive correlations were found between parental education, health conditions, and parental involvement with attendance patterns, highlighting their crucial impact on student attendance. Contrarily, distance to school showed a non-significant correlation with attendance rates. The study underscores the significance of parental support, health considerations, and a supportive learning environment in promoting positive student attendance and academic outcomes. Recommendations include enhancing parental education programs, implementing health support initiatives, and strengthening parental involvement strategies to improve attendance rates and foster academic success. This research provides valuable insights for stakeholders, including the Department of Education, school administrators, teachers, students, parents, community members, and future researchers, aiming to address absenteeism effectively among 4Ps beneficiary-students.